Implementasi Program Pendidikan Melalui Pembuatan Media Belajar di Rumah Singgah Mawaridi Kelurahan Pacar Kembang - Limbono, Stefani; Supriyanti , Ides; Lasakar, Yesisca; Yudha, Ramdhan; Marcel, Laurensius; Lorensza, Meisye (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2024)
This Community Service activity was carried out by students at the Mawari Halfway House, Surabaya, with the aim of improving the quality of education for underprivileged children. This program involves creating various learning media such as series and parallel electrical circuits, replicas of solar systems, as well as information about provinces in Indonesia. This activity not only increases children's interest and motivation to learn, but also develops cooperation, social awareness and students' ability to interact with the community. As a result, this activity provided a significant positive contribution for both parties.